Propiedades biológicas y farmacológicas en los aceites esenciales de semillas oleaginosas - López Aguirre, Genesis Estefanía (2024)
Essential oils are mixtures of aromatic substances obtained from various plants, where about 4000 different spices are known in the world. Although not all plants contain this substance, most of their seeds are an important source of oils, which has generated interest in scientific research, food industry and pharmaceutical industry due to their high properties. The objetive was to analyze the biological and pharmacological properties of essential oils from oliseeds. This Project has been elaborated by collecting all kinds of information through research and analysis of varius websites, books, scientific articles, journals available on varius digital platforms. This Project addresses the development of plants such as sunflower, soybean and avocado for essential oils, highlighting their characteristics benefits and possible uses. It is mentioned that sunflower is a herbaceous plant, where we can extract its essential oils that includes nutritional properties such as polyunsaturated fatty acids that are beneficial to health. In addition, it is highlighted that soybean essential oils has isoflavones that provide benefits for the skin, prevent cardiovascular diseases and reduce csholesterol levels, among other posstive effects. On the other hand, avocado essential oil stands out for its anticarcinogenic and antioxidant properties, as well as its ability to block the growth of cancer cells. The importance of these essential oils in various industries, such as food and cosmetics, is also mentioned, due to their antioxidant activity and beneficial properties. It is also noted that Ecuador has been an important exporter and importer of essential oils, with an estimated growth in world production by 2025.